Re: Mediators of the Effect of Body Mass Index on Coronary Heart Disease. Issue 3 (May 2016) - Fritz, Josef; Strohmaier, Susanne; Nagel, Gabriele; Concin, Hans; Ulmer, Hanno
Abstract : Supplemental Digital Content is available in the text.